The study of characterization in the Siraiki folk tales - Muhammad Mumtaz Khan; Jawed Hassaan Chandio (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2015)
Characters hold a significant place in the structure of a tale. Many of the characters in the verse romantic tales or ballads of the Siraiki language are real. These tales are not confined to the description of love related themes or of adventures. These tales also deal with history, collective social behaviors, human relations, emotions, customs and traditions, beliefs, landscape, the depiction of different sections of society as well as the internal social system. The characters of verse tales highlight the cultural and intellectual aspects of the society. The present study is to conduct the intellectual, symbolic, social and cultural analyses of the characters in the selected Siraiki verse tales of Heer Ranjha.
Keywords: 330; Folk literature; history; symbolic; social and cultural; customs and traditions; feudalistic; characters; behaviours; beliefs